2016
DOI: 10.1002/btm2.10037
|View full text |Cite
|
Sign up to set email alerts
|

Integration of growth factor gene delivery with collagen‐triggered wound repair cascades using collagen‐mimetic peptides

Abstract: Growth factors (GFs) play vital roles in wound repair. Many GF therapies have reached clinical trials, but success has been hindered by safety concerns and a lack of efficacy. Previously, we presented an approach to produce protein factors in wound beds through localized gene delivery mediated by biomimetic peptides. Modification of polyethylenimine (PEI) DNA polyplexes with collagen‐mimetic peptides (CMPs) enabled tailoring of polyplex release/retention and improved gene transfer activity in a cell‐responsive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 68 publications
(194 reference statements)
1
25
0
Order By: Relevance
“…MMP activity mediated polyplex release through collagen degradation, and polyplex release could be modulated based upon the CMP conjugation ratio (0% to 50% CMP-PEI) to extend release from 20 days (for 0% CMP-PEI) to 35 days (for 50% CMP-PEI) [46]. In vitro wound closure with PDGF polyplexes was improved by 2-fold and 2.5-fold with 20% CMP-PEI polyplexes and mixed polyplexes (20% CMP-PEI and 50% CMP-PEI mixtures), respectively, as compared to non-CMP-modified polyplexes [47]. On-demand polyplex release and gene expression delivery was also were demonstrated in vivo , wherein gene expression could be tailored to peak at 6-20 days depending on the levels of CMP modification [48].…”
Section: Peptides For Spatiotemporally-controlled Gene Deliverymentioning
confidence: 99%
“…MMP activity mediated polyplex release through collagen degradation, and polyplex release could be modulated based upon the CMP conjugation ratio (0% to 50% CMP-PEI) to extend release from 20 days (for 0% CMP-PEI) to 35 days (for 50% CMP-PEI) [46]. In vitro wound closure with PDGF polyplexes was improved by 2-fold and 2.5-fold with 20% CMP-PEI polyplexes and mixed polyplexes (20% CMP-PEI and 50% CMP-PEI mixtures), respectively, as compared to non-CMP-modified polyplexes [47]. On-demand polyplex release and gene expression delivery was also were demonstrated in vivo , wherein gene expression could be tailored to peak at 6-20 days depending on the levels of CMP modification [48].…”
Section: Peptides For Spatiotemporally-controlled Gene Deliverymentioning
confidence: 99%
“…Hybrid hydrogels offer expanded opportunities in biomedical applications by enabling modulation of microscale hydrogel properties (suitable for cell adhesion, migration, and proliferation) as well as the inclusion and tailoring of drug or gene delivery features (suitable for microenvironment-sensitive and targeted therapy) ( Figure 5). They have been employed as therapeutic interventions in a variety of conditions including wound healing [71,72], osteogenesis [51,73], cancers [39,74], myocardial infarction [75], Parkinson's disease [76], and infections [77,78] along with the development of biodevices and biosensors or contact lenses [79].…”
Section: Biomedical Applications Of Hybrid Hydrogelsmentioning
confidence: 99%
“…Of particular interest are hydrogels that incorporate biologically inspired molecules and delivery methods. A collagen mimetic peptide (CMP)-polyplex mediated delivery of platelet-derived growth factor-BB (PDGF-BB) genes from collagen gels improved PDGF-BB expression and promoted a diverse range of cellular processes associated with wound healing, including proliferation, extracellular matrix production, and chemotaxis [72]. An injectable form of heat shock protein 27 (HSP27, molecular chaperones that protect heart muscle from ischemic injury) fused with TAT peptide and contained in a hybrid hydrogel system composed of poly(lactic-co-glycolic acid) (PLGA) microsphere and alginate hydrogel sustained the release of HSP27 for two weeks in vitro based on the pore size [75].…”
Section: Biomedical Applications Of Hybrid Hydrogelsmentioning
confidence: 99%
“…These observations suggested that the immobilized polyplex on the hydrogel enhanced and sustained the transgene expression over 30 days of cell culture, compared to a non-coated bolus transfection (Figure 5B). In addition to these two strategies for non-covalent immobilization of poyplex to ECM hydrogels, our group has developed approaches to immobilize polyplexes in collagen hydrogels through interactions with collagen-mimetic peptides [e.g., GPP: (GPP) 3 GPRGEKGERGPR(GPP) 3 GPCCG] that have affinity for native collagen through strand invasion and triple-helical binding (Urello et al, 2014(Urello et al, , 2016. With higher amounts of GPP incorporated in the polyplex, the polyplex was retained in the hydrogel longer, with retention up to 35 days (Urello et al, 2014).…”
Section: Ecm-based Matrix and Carrier Interaction For Intracellular Dmentioning
confidence: 99%